Synthesis of NiAl and Mo/NiAl catalysts for the production of sustainable fuels - Marcelino, Maria do Carmo; González, Juan Felipe; B.M. Barbosa, Celmy; A. Pacheco, José Geraldo; Arias, Santiago; Fréty, Roger; Stragevitch, Luiz; R. Carvalho, Florival (XIV Encontro de Catálise do Norte, Nordeste e Centro-Oeste, 2024)
Due to the environmental impact caused by the burning of fossil fuels, the production of biofuels from catalytic deoxygenation of vegetable oils stands out as a promising strategy for energy transition [1]. In this context, the catalyst is essential to ensure high conversion and selectivity, with emphasis on nickel (Ni) catalysts, which have high thermal and chemical stability and high hydrogenation activity, facilitating deoxygenation. Molybdenum (Mo), on the other hand, has low electronic density andhigh electronegativity, which increases deoxygenation efficiency and acts synergistically with Ni, enhancing its catalytic activity. The use of high aluminum (Al) content favors the formation of mixed oxides with a large surface area, basicity, and thermal stability, and allows phase segregation, improving Ni dispersion and increasing its resistance to sintering [2,3]. Thiswork is about the synthesis and characterization of the NiAl catalyst derived from layered double hydroxides (LDH) with high aluminum content. The precursor with composition Ni0,2Al0,8(OH)2(TA)0,4·mH2O was synthesized by the slow addition of metal nitrates and terephthalic acid solutions in NaOH (1M) to boiled deionized water (65 °C) under constant stirring and pH. The precipitate was kept under agitation and heating for 4 hours and then at room temperature for 18 hours. After filtration andwashing, the material was dried in an oven at 100 °C overnight and calcined at 600 °C for 3 hours at a heating rate of 10 °C min⁻¹, forming the NiAl mixed oxide catalyst, which was also used as a support for the impregnation of 15% molybdenum by the wet method with an ammonium heptamolybdate solution ((NH4)6Mo7O24) and later calcined to obtain the Mo/NiAl catalyst. The materials were characterized by XRD, TGA, NH3-TPD, H2-TPR, FTIR, EDX, and N2 adsorption/desorption. TGA established 500 °C as the minimum calcination temperature. X-ray diffractograms confirmed the formation of NiAl LDH and the mixed oxide (with NiO and NiAl2O4 phases) after calcination. H2-TPR analysis confirmed the presence of molybdenum, which increased the catalyst's reducibility (VTPR-NiAl = 663,9 mL H2/g e VTPR-Mo/NiAl = 1098 mL H2/g). With the addition of molybdenum, the surface area and pore volume slightly decreased (SNiAl = 225 m²/g, SMo/NiAl = 215 m²/g, Vp-NiAl = 0,6 cm³/g e Vp-Mo/NiAl = 0,5 cm³/g). TPD analysis showed that the NiAl catalyst has a higher density of acidic groups (1230.9 µmol NH₃/g) compared to Mo/NiAl (709.0 µmol NH₃/g), attributed to the reduction of stronger acid sites. Therefore, the results of the analyses indicate that both NiAl and Mo/NiAl have promising characteristics for use as catalysts in catalytic deoxygenation reactions.